AKTIFITAS PEMBELAJARAN STEM SISWA SEKOLAH DASAR: MEMBUAT PEMBANGKIT LISTRIK TENAGA SURYA SEBAGAI SUMBER ENERGI ALTERNATIF - Daswarman, Daswarman; Koes Handayanto, Supriyono (Riau Education Journal, 2021)
This paper is about STEM learning activities in the manufacture of solar power plants as an alternative energy source. Learning development by integrating physics and mathematics lessons as well as engineering design to overcome the limitations of electrical energy. The STEM learning activities that will be developed are based on the STEM learning approach by Sutaphan and Yuenyong. This problem will be solved through a project by students. The limited sources of electrical energy in remote areas can be solved by making solar power plants. This solar power plant utilizes solar energy. Through STEM learning, elementary school students are expected to be able to collaborate in applying knowledge about physics, mathematics and engineering design. To make this engineering design, students can take advantage of their knowledge of electrical circuits, engineering design about sizes suitable for installation as well as mathematical calculations. This paper is expected to be able to design STEM learning activities.